Six new Stenus species of the cirrus group (Coleoptera, Staphylinidae) from China with a key to species of the group - Liang, Tang; Zhao, Yun-Long; Puthz, Volker (Zootaxa, 2008)
Six new Stenus species of the cirrus group are described from China: S. zhulilongi Tang & Puthz, sp. nov., S. jiulongshanus Tang & Puthz, sp. nov. and S. shenshanjiai Tang & Puthz, sp. nov. from Zhejiang Prov., S. lijinweni Tang & Puthz, sp. nov. from Zhejiang and Jiangxi Prov., S. flammeus Tang & Puthz, sp. nov. and S. bostrychus Tang & Puthz, sp. nov. from Sichuan Prov., and their diagnostic characters are illustrated. The male of S. cirrus L. Benick, 1940 was found and illustrated for the first time. A key to species of the cirrus group is provided. All six new species have diagnostic characters of the subgenus Hypostenus. Some species of this group, including S. cirrus, fit the concept of the subgenus Hemistenus.